Von der Vielfalt der ägyptischen Sprache in der griechisch-römischen Zeit - Quack, Joachim Friedrich (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
In this article the discussion is continued, in answer to a position of Dieter Kurth, if it is justified to speak of a specific ‘Ptolemaic’ phase of Egyptian language. Current models of the development of written and spoken Egyptian are discussed and shown to be insufficient in view of the complexity of the actual attestations. In particular, it is not possible to postulate a simple binary opposition with a situation of ‘diglossia’. Rather, the full spectrum of different stages of the Egyptian language can turn up in texts attested in the later periods. A number of cases is brought forth in order to demonstrate that the Egyptian did not consider ‘classical’ Egyptian to be obligatory for religious compositions. Given that Egyptian temple inscriptions of the Graeco-Roman period are linguistically not homogenous, it is not possible to define ‘Ptolemaic’ as a specific phase of the language.